Different Output Ripples of Speed and Torque and Output Ripple Minimization for External Hydraulic Gear-motors - Li Yulong; Hou Xinyu; Zhang Lihua; Song Anran (Jixie chuandong)
In order to improve the output pulsation research of gear-motor existing deficiencies, a set of the efficient analytical method is established to minimize its output ripple. Firstly, from the flow ripple formula of the gear-pump, the speed and torque ripple formula of the gear-motor are derived, and the corresponding differentiation discrimination is carried out. Secondly, the relation between the minimum output ripple and the maximum tooth number and the maximum contact ratio is analyzed theoretically. Finally, based on the structural characteristics of the tooth profile without undercut, the corresponding tooth profile parameters under the minimum output ripple are derived by the analytic method using the maximum addendum pressure angle and the minimum addendum center angle. The results show that the motor torque and pump flow rate have the same theoretical pulsation coefficient, but are smaller than the theoretical pulsation coefficient of the speed. The minimization of output pulsation is equivalent to the maximization of the coincidence degree, and the maximization of the coincidence degree is equivalent to the maximization of the tooth top pressure angle and the tooth number. The maximum allowable tooth tip pressure angle and the minimum tooth tip center angle are two key performance parameters that determine the degree of output pulsation minimization. The tooth profile parameters can be obtained through analytical methods from both, thus correcting the existing classical conclusion that the output speed/torque of gear motors have the same pulsation coefficient.